Kegagalan internalisasi nilai dalam pendidikan agama Islam: Analisis konseptual kesenjangan antara pengetahuan dan praktik ibadah siswa - Siti Aisyah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2026)
This study examines the phenomenon of value internalization failure in Islamic Religious Education (PAI) learning, manifested in the significant gap between students' religious knowledge mastery and the quality of their worship practice. Through a library research approach employing content analysis and multidisciplinary critical analysis, this study integrates four theoretical frameworks: Krathwohl's affective taxonomy, Bandura's moral disengagement theory, Al-Ghazali's pedagogical epistemology, and Bronfenbrenner's ecological systems theory. Findings reveal that internalization failure operates systemically across three interacting levels: (1) micro-individual characterized by low intrinsic motivation and active moral disengagement mechanisms; (2) meso-institutional marked by the dominance of cognitive approaches, non-affective teaching methods, and the reduction of teachers' roles to mere transmitters; and (3) macro-ecological reflected in value inconsistencies across school, family, and digital culture ecosystems. This study proposes the PAI Value Internalization Model (MIVPA), mapping internalization as a five-phase process: cognition, affection, reflection, commitment, and habituation with concrete implications for pedagogical reform, assessment systems, and Islamic religious education policy at large.